Dietary Supplement of Moringa Oleifera Leaf Meal on Growth Performance and Carcass quality of Grower Broilers - Coleman Fred Newman; Yakubu Ansoba Emmanuel; Oppong Darkwah Jerry; Nkwantabisa Gideon; Baturi Stephen; Boadu Solomon; Sarkwa Felix Owusu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
This study was conducted to assess the impact of Moringa oleifera leaf meal (MoLM) on the growth performance and carcass quality of broiler chickens at the growing and finishing stages. Fresh Moringa olefera leaves purchased was washed and air dried for two weeks, milled and incorporated into feed. A total of 108 twenty-eight day-broiler chicks of initial average weight of 940g were used in this experiment. Birds were randomly assigned to three treatments of 36 birds each. Each treatment was sub divided into three replicates of 12 birds each. The three treatments were designated T1(0% MoLM), T2(T 1 + 1% MoLM) and T3 (T1 + 3% MoLM). The experiment lasted for 28 days. Dietary treatments, were labelled as T1 (0% MoLM), T2 (T 1 + 1% MoLM) and T3 (T1 + 3% MoLM). Feeding and watering of birds were served ad-libitum. Productive performance and carcass characteristics of experimental birds were measured. 1 % MoLM diet had the best feed conversion ratio, whiles those on the 3% MoML diet recorded the highest average body weight gain. Carcass analysis indicated that the birds on the 3% MoLM diet had the highest dressing percentage. Sensory evaluation parameters were significantly improved by the inclusion of 3%MoLMin the diet. The 3% MoLM breast cut grilled meat produced highest overall likeness and product intended to buy mean vales. In conclusion, MoLM inclusion to broiler diets up to 3% improved birds’ performance at growing stage. After week 4, the growth promoting property of MoLM was not observed.